Influence of Mineral Fertilizer and Manure Application on the Yield and Quality of Maize in Relation to Intercropping in the Southeast Republic of Kazakhstan - Maksat Batyrbek; Fakher Abbas; Ruqin Fan; Qingfang Han (Plants, 2022)
Maize (Zea mays L.) is a valuable forage crop. It is also an essential and promising crop for the Republic of Kazakhstan, cultivated in the southern zone. Some new maize hybrids have been introduced, which have been beneficial for high yields with less fertilizer input. This study aims to introduce the new maize hybrid, Arman 689, for the judicial use of fertilizer and the high yield. This study was carried out in 2015 in the southeast region of Kazakhstan. There are five treatments with various mineral fertilizer and poultry manure doses: 1. control (T0), 2. P60 K100 (T1), 3. N100P60K100 (T2). 4. N100P60K100 + 40 tons of manure/ha (T3), and 5. N100P60K100 + 60 ton of manure/ha (T4). The fertilizers used were ammonium nitrate (N—34.6%), amorphous (N—11.0%, P2O5—46.0%), and potassium chloride KCl (K2O—56%). The results showed that the grain yield ranges from 5.51 t/ha (T0) to 8.49 (T4) t/ha. The protein contents in the maize grain varied from 9%(T0)–11.3%(T4). The grain nitrogen content accounted for 54.2 to 52.0%. The nutrient uptake results by different treatments indicated that nitrogen contributed to 41.5% of the total yield increase. Using manure in combination with mineral fertilizers reduced the payback of the applied resources, as the payback of T2–T4 was 8.8–9.1 kg of grain. With the application of recommended mineral fertilizer (NPK), the protein yield was 0.83 t/ha, 0.33, and 1.22 t/ha higher than T0 and T1 treatments, respectively. There was no significant yield difference under T3 and T4 treatments (p > 0.05). Overall, the treatment, NPK + 40 tons of manure, was proved the ultimate for the Arman hybrid in providing the optimum quantity and quality of maize, as well as reducing the payback cost (8.8–9.1 kg of grain). It is suggested to apply NPK-recommended doses along with manure in maize (Arman hybrid)-based intercropping systems to utilize the resources efficiently.